Incidence of locally advanced breast cancer in women presenting to a tertiary care center - Ramani, Pratha Anantha; Niharika, Vadisetti Satya; Maha Lakhsmi, Buddha Kanaka; Jahnavi, Suvarapu; Sainath Reddy, Ginni Vijay (International Surgery Journal, 2019)
Background: Trends for incidence of breast cancer are on the rise in India. However, regional specific epidemiological data for North Coastal Andhra Pradesh are inadequate. The study aims to stress upon the trends of the incidence and burden of locally advanced breast cancer in the region. Methods: In a retrospective quantitative study, 310 in-patients of Department of General Surgery, King George Hospital diagnosed with breast cancer whose information is in the medical records covering the calendar period from May 2014 to May 2019 were studied. Results: The number of females being admitted as in-patients for treatment of breast cancer has increased from 11.2% to 13.6% in these five years. The overall result showed that the age of breast cancer patients ranged from 28-74 years, with a mean age of 49.12±10.942. The average duration of time lag to contact with health personnel was 3.6 months for all the cases included in our study. Stage III was the most common presentation constituting 55.01% patients of the series. Most common cause for late presentation was lack of awareness (64.5%) followed by emotional reasons and cultural barriers (31.9%). Conclusions: There is an urgent need for implementation of measures to ensure early presentation as prevention of LABC is much better than cure.